Reconfiguração de redes de distribuição de energia considerando variáveis multiatributo no desenvolvimento de novas topologias - Timossi, Marcelo Santiago (2016)
Smart grids have emerged as one of the key players in restructuring the electric power system has been suffering for some years. More specifically, this evolution has taken prominence in the electricity distribution networks. The emergence of new equipment with modern technology allows the system to be monitored in real time and operated remotely by the needs. In order to optimize more and more features of the equipment, applying and promoting systems that function autonomously is that research is developing new methodologies to meet the needs of restoration of distribution networks on the abnormality. A new concept that has emerged as component of smart grids has been moving the academic sector and the utilities responsible for distribution of energy called reconfiguration of distribution networks, has discussions and studies theme being on the best deployment of alternatives. This thesis presents a model for use in reconfiguring based systems, identifying the best results for the set when you need to load transfer of a loss of power substation in their power supplies. The model takes into account the main quality indicators and energy continuity obtained from an exhaustive search method selecting the best options maneuvers to reconfigure feeders by an anomaly in the distribution system. The multicriteria method PROMETHEE is used to define the best maneuver sequences on the network and therefore the best performance for the system after the relocation of cargo. The model presents a characteristic slightly different from that found in the literature, it does not use any compensation method for improving the rates of voltage levels and energy losses. The proposed methodology was evaluated and validity by simulations in a real network belonging to an electric utility and the results showed a significant improvement to the distribution system.